Implement differentiation strategy By Using Sustainable Costs Management Techniques (Applied study) - Hadi Mahdi, Zainab (JOM, 2024)
Research aims to study one of the costly administrative technologies,which is a sustainable costs management techniques and highlighting itsrole in reducing costs and shortening the life cycle of the product andmeeting the requirements of customers and focusing on theenvironmental dimension and indicating its impact on the implementationof one of the competitive strategies, which is the strategy of differentiation.The research is classified as a study Applied in the Diwaniyah tires factoryaffiliated to the General Company for Rubber Industries, and the researchreached a set of conclusions, the most important of which are: thenecessity of applying the sustainable synchronous engineering in theresearch sample factory because of the benefits of this technology inachieving savings in the time, cost and quality, which in turn is in line withthe distinction strategy as well as the necessity of following this Thestrategy to obtain a greater market share and thus achieve higher profits,which contributes to the recovery of the national economy.